KONSTRUKSI BERITA PEREMPUAN DI MEDIA ONLINE Tirto.id (Analisis Framing Pemberitaan Kasus Pelecehean Seksual terhadap Perempuan Selebriti dan Non-Selebriti Periode Januari-November 2018) - Kartikasari, Bunga Wahyu; Wibawa, Arif (Paradigma: Jurnal Masalah Sosial, Politik, dan Kebijakan, 2018)
There are many mass media in Indonesia which is not implementating the concept of equality gender yet, especially news about sexual harassment. Whereas, the framing of mass media can drive people to do like what they want. That’s why, we need more news which support gender perspective and educate people about equality. So, the sexual harrasment won’t be seen as a normal thing happened. This research focuses to the news framing in online media Tirto.id under the hastag sexual harrasment. Constructivism theory is used in this research which is emphasized the reality is plural and subjective. Researcher takes 18 from 67 articles to be analysed using Robert Entman’s framing method. Entman’s method focuses to four things, problems identification, casual interpretation, make moral judgement dan treatment recommendation. The result of this research is Tirto.id already implementated gender perspective journalism which was not brought the woman down but also didn’t blame the men. Tirto.id constructs women as the one who’s equal, smart and independent, but there’s an inequality of gender between men and women. That’s why women are kind of powerless that make them a victim of sexual harassment. For the news in celebrity corner, Tirto.id tried to educate readers how to respond to the sexual harassment. Meanwhile, in the non celebrity corner, there are many critics said to the related institution as the way to enforcement the concept of gender equality.